Ficoll‐hypaque separation vs whole blood lysis: Comparison of efficiency and impact on minimal residual disease analysis. (4th December 2017) - Genuardi, E.; Barbero, D.; Dogliotti, I.; Mantoan, B.; Drandi, D.; Gambella, M.; Zaccaria, G. M.; Monitillo, L.; Della Starza, I.; Cavalli, M.; De Novi, L. A.; Ciabatti, E.; et al.
Abstract: Introduction: The high‐throughput era remarkably changed molecular laboratory practice. Actually, the increasing number of processed samples requires to reduce the risk of operator biases, by automating or simplifying as much as possible both the analytical and the pre‐analytical phases. Minimal residual disease (MRD) studies in hematology often require a simultaneous processing of many bone marrow and peripheral blood samples from patients enrolled in prospective, multicenter, clinical trials, monitored at several planned time points. Methods: In this study, we demonstrate that red blood cell lysis (RBL) pre‐analytical procedure can replace the time‐consuming Ficoll stratification as cell recovering step. Here, we show a MRD comparison study using both total white blood cells and mononuclear cells recovered by the 2 procedures from 46 follicular lymphoma (FL), 15 multiple myeloma (MM), and 11 mantle cell lymphoma (MCL) patients enrolled in prospective clinical trials. Results: The experiments were performed in the 4 laboratories of the Fondazione Italiana Linfomi (FIL) MRD Network and showed superimposable results, in terms of good correlation ( R  =   0.87) of the MRD data obtained by recovering blood cells by the 2 approaches. Conclusion: Based on these results, the FIL MRD Network suggests to optimize the pre‐analytical phases introducing RBL approach for cell recovery in the clinical trials including MRD analysis.